Propuesta de una Unidad de Gestión de Proyectos y Mejora de Procesos en el Consejo Nacional de Rectores - Alfaro-Cervantes, Luis Diego; Ugalde-Campos, Natalia (Instituto Tecnológico de Costa Rica, 2011)
Since year 2005, as result of the negotiation of the FEES IV Financing Convention; which defines how resources should be assigned to the development of interuniversity projects, that impact or benefit the Costa Rican society, CONARE has been responsible for the management of those projects. Currently, there are one hundred and thirty-four projects running with a budget of ¢18.449 million. However, the current project management is not being developed by a Professional Project Management. Therefore, the purpose of this research is to provide a plan for a Project Management Office and a proposal for process improvement. The methodology used was based to identify the current status of project management at CONARE by measuring the level of maturity and a survey applied to the project owners. Also good practices on project management were identified from entities of different countries with similar lines of management as CONARE and the PMI Standard Portfolio. The results are oriented to improve the integration and standardization of the processes of portfolio management at CONARE. Thus, propose a plan that includes a Project Management Office and improving processes.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2011.
Keywords: Administración; Gestión de proyectos; Portafolio de proyectos; CONARE